2007
DOI: 10.1111/j.1365-2621.2006.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of retailed organic, free‐range and conventional chicken breasts

Abstract: Lipid fractions of 20 retailed chicken breasts were correlated with production system: organic, corn-fed, free-range and conventional. Neutral lipid (NL), phospholipid (PL) and free fatty acids (FFA) were examined separately. Influence of production systems was found more pronounced in PL composition than NLs. Corn-fed and free-range NLs had higher contents of nutritionally beneficial eicosapentanoic acid (C20:5 n-3) and docosahexanoic acid (C22:6 n-3) than organic and conventional. Lower polyunsaturated fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The review of Minihane et al (2008) identified only eight truly organic vs. conventional study comparisons for fatty acids in chicken meat with most studies reporting only fatty acid profile (Castellini, Mugnai and Dal Bosco, 2002) or fatty acids in phospholipid and neutral lipids fractions (Jahan and Paterson, 2007) and not in whole edible cooked meat. Fat from organic meat in the present study contained a higher concentration of SFA (mainly 16:0), n-6 PUFA (mainly 18:2) and long chain n-3 PUFA (notably EPA and DHA) but a lower concentration of cis-MUFA than meat from conventionally produced birds.…”
Section: Discussionmentioning
confidence: 99%
“…The review of Minihane et al (2008) identified only eight truly organic vs. conventional study comparisons for fatty acids in chicken meat with most studies reporting only fatty acid profile (Castellini, Mugnai and Dal Bosco, 2002) or fatty acids in phospholipid and neutral lipids fractions (Jahan and Paterson, 2007) and not in whole edible cooked meat. Fat from organic meat in the present study contained a higher concentration of SFA (mainly 16:0), n-6 PUFA (mainly 18:2) and long chain n-3 PUFA (notably EPA and DHA) but a lower concentration of cis-MUFA than meat from conventionally produced birds.…”
Section: Discussionmentioning
confidence: 99%
“…As consumer interest and demand for organic muscle food increase, a better understanding of the oxidative stability and nutritional aspects of organic meat production is essential. The data reported in the recent studies are referred mostly to poultry and beef meat (Enser et al, 1998;Castellini et al, 2002;Nuernberg et al, 2002;Jahan & Paterson, 2007;Husak et al, 2008). However, to our knowledge, little information relative to organic pig meat is currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding lipid and fatty acid research, their extraction from either plant or animal sources uses traditional analytical methods. The procedure usually requires a relatively long time and often conventional solvents, normally chloroform (CHCl 3 ) . Other solvents such as hexane have also been employed but with lesser efficacy .…”
Section: Introductionmentioning
confidence: 99%